Insomnia Symptoms and Acute Coronary Syndrome-Induced Posttraumatic Stress Symptoms: A Comprehensive Analysis of Cross-sectional and Prospective Associations. Issue 10 (13th February 2021) - von Känel, Roland; Meister-Langraf, Rebecca E; Pazhenkottil, Aju P; Barth, Jürgen; Schnyder, Ulrich; Schmid, Jean-Paul; Znoj, Hansjörg; Princip, Mary
Abstract: Background: Acute coronary syndrome (ACS) induces clinically significant posttraumatic stress symptoms (PTSS) in 12% of patients. Subjective sleep problems are a risk factor for the development of PTSS, but this is underexplored in patients with ACS. Purpose: To examine the association of insomnia symptoms with ACS-induced PTSS. Methods: In this longitudinal study with 154 patients (all white, 84.4% male, mean age 58.7 years) with a verified ACS, insomnia symptoms were interviewer assessed at hospital admission and at 3 months, using the Jenkins Sleep Scale (JSS)-4. ACS-induced PTSS were assessed with the Clinician-Administered Posttraumatic Stress Disorder Scale 3 months after hospital admission. In multivariable linear models, insomnia symptoms were regressed on PTSS, adjusting for demographics, clinical variables, health behaviors, and psychological data, including cognitive depressive symptoms. Results: Greater insomnia symptoms at admission (β = .165, p = .034), greater increase in insomnia symptoms from admission to 3 months (β = .233, p = .008), and greater insomnia symptoms at 3 months (β = .239, p = .002) were independently associated with more severe total PTSS at 3 months. Concerning the individual PTSS clusters, both insomnia symptoms at admission (β = .214, p = .007) and at 3 months (β = .213, p = .012) were independently associated with reeexperiencing symptoms. Removing sleep items from PTSS scores and excluding patients on antidepressants in two sensitivity analyses did not substantially change the results. Conclusions: Insomnia symptoms could play an important role in the development and severity of ACS-induced PTSS. This relationship seems not simply explained by the fact that sleeping difficulties are inherent to the phenotype of posttraumatic stress disorder. Clinical Trial information: NCT01781247. Abstract : Patients with acute myocardial infarction and more sleep problems on hospital admission, and in the period thereafter, developed more myocardial infarction-induced posttraumatic stress.